Rediscover and Refine QTLs for Pig Scrotal Hernia by Increasing a Specially Designed F3 Population and Using Whole-Genome Sequence Imputation Technology - Xu, Wenwu; Chen, Dong; Yan, Guorong; Xiao, Shijun; Huang, Tao; Zhang, Zhiyan; Huang, Lusheng (Frontiers in Genetics, 2019)
Pig scrotal hernia is one of the most common congenital defect triggered by both genetic and environmental factors, leading to severe economic loss as well as poor animal welfare in the pig industry. Identification and implementation of genomic regions controlling scrotal hernia in breeding is of great appeal to reduce incidences of hernia in pig production. The aim of this study was to identify such regions or molecular markers affecting scrotal hernia in pigs. First of all, we summarizing the results of some international teams on scrotal hernia and designed a specially population after analyzing. Then performed genome-wide association study (GWAS) in this Specially Designed Population in two scenarios, i.e., the target panel data before and after imputation. In addition, a series of methods including genetic differentiation analysis, Linkage disequilibrium and linkage analysis (LDLA) and haplotype sharing analysis were appropriate to provide for further analysis to identify the potential gene underlying the QTL. The GWAS in this report detected a highly significant region affecting scrotal hernia within a 24.8Mb region (114.1-138.9Mb) on SSC8. And the result of genetic differentiation analysis also showed a strong genetic differentiation signal between 116.1 and 132.7Mb on SSC8. In addition, the QTL interval was refined to 2.99Mb by combining LDLA and genetic differentiation analysis. Finally, two susceptibility haplotypes were identified through haplotype sharing analysis, with one potential causal gene in it. Our study provided deeper insights into the genetic architecture of pig scrotal hernia and contributed to further fine-mapping and characterize haplotype and gene that influence scrotal hernia in pigs.